Menggali Makna Penerapan Akuntansi Lingkungan dalam Pengelolaan Limbah Rumah Sakit - Novrida Qudsi Lutfillah; Yustin Nur Fauziah; Jaswadi Jaswadi (JIATAX (Journal of Islamic Accounting and Tax), 2021)
The purpose of this study is to reveal the value in the application of environmental accounting for hospital waste management. This type of qualitative research with the object under study is Muhammadiyah Hospital Lamongan. The results show that the hospital has managed hospital waste according to the rules, it's just that the waste management transaction has not been made a separate report. The application of environmental accounting at Lamongan Muhammadiyah Hospital is a form of hospital responsibility towards the environment based on the values of Istiqomah and Amanah.